2011
DOI: 10.1111/j.1464-0597.2011.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

For Fun, Love, or Money: What Drives Workaholic, Engaged, and Burned‐Out Employees at Work?

Abstract: Previous research has distinguished between two types of working hard: workaholism, a "bad" type of working hard, and work engagement, a "good" type of working hard. However, the motivations underlying workaholism and work engagement have not been examined extensively. Building on Deci and Ryan's Self-Determination Theory, the present study examined the motivational correlates of workaholism, work engagement, and burnout (a possible consequence of working hard), using data from Chinese health care professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
262
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(288 citation statements)
references
References 52 publications
(81 reference statements)
17
262
0
9
Order By: Relevance
“…Są one pozytywne, głównie między pracoholizmem a wyczerpaniem (Andreassen i in., 2007;Guglielmi i in., 2012;Schaufeli i in., 2008;Taris i in., 2005;van Beek i in., 2012). W odniesieniu natomiast do związków składo-wych pracoholizmu z wypaleniem zawodowym znajdujemy sprzeczne dane.…”
Section: Stan Badań Nad Związkami Między Pracoholizmem I Wypaleniemunclassified
See 3 more Smart Citations
“…Są one pozytywne, głównie między pracoholizmem a wyczerpaniem (Andreassen i in., 2007;Guglielmi i in., 2012;Schaufeli i in., 2008;Taris i in., 2005;van Beek i in., 2012). W odniesieniu natomiast do związków składo-wych pracoholizmu z wypaleniem zawodowym znajdujemy sprzeczne dane.…”
Section: Stan Badań Nad Związkami Między Pracoholizmem I Wypaleniemunclassified
“…W odniesieniu natomiast do związków składo-wych pracoholizmu z wypaleniem zawodowym znajdujemy sprzeczne dane. W zależności od badania, najsilniejsze związki notowane są między wypaleniem i emocjonalnymi (Andreassen i in., 2007), poznawczymi (Burke i Matthiesen, 2004;Schaufeli, Bakker i in., 2009;Schaufeli i in., 2008) lub behawioralnymi (Guglielmi i in., 2012;van Beek i in., 2012) wskaźnikami pracoholizmu (zob. Tabela 1).…”
Section: Stan Badań Nad Związkami Między Pracoholizmem I Wypaleniemunclassified
See 2 more Smart Citations
“…The therapeutic relationships that nurses develop with patients entail an ongoing and intense level of personal emotional contact that may potentially cause an erosion of a positive psychological state [1]. Previous studies suggest that the emotional labour characterising the everyday practice of human service professionals, including nurses, may be a prominent factor when predicting burnout among nurses and have a higher effect than more common job stressors [14] [15]. It is suggested that nurses experiencing burnout are deviant in the sense that they act without intent or refrain from acting while distancing themselves from their work in order to prevent further reduction of mental resources [14] [15].…”
Section: Introductionmentioning
confidence: 99%